Research on Moringa (Moringa oleifera Lam.) in Africa - El Bilali, Hamid; Dan Guimbo, Iro; Nanema, Romaric Kiswendsida; Falalou, Hamidou; Kiebre, Zakaria; Rokka, Veli-Matti; Tietiambou, Sheirita Reine Fanta; Nanema, Jacques; Dambo, Lawali; Grazioli, Francesca; Naino Jika, Abdel Kader; Gonnella, Maria; et al. (MDPI, 2024)
While Moringa oleifera Lam. is gaining importance in Africa, especially sub-Saharan Africa, it is unclear whether research is following the quick pace of its development on the continent. Therefore, this article analyzes the landscape of research dealing with moringa in Africa. This systematic review draws upon 299 eligible articles identified through a search carried out on the Web of Science in April 2023. Research on M. oleifera is rather recent in Africa but interest is increasing among scholars. While the research field is multidisciplinary and cross-sectoral, the literature seems to focus on biological and environmental sciences. Moreover, research is performed mainly in South Africa, Nigeria, Egypt, and Ghana. The analysis suggests a significant potential contribution of moringa to food security and nutrition, climate change mitigation/adaptation, farming systems resilience, and livelihoods. Its versatility and diverse applications and uses make moringa particularly interesting for developing countries, such as African ones. However, this review also underscores some factors hindering its development. Therefore, there is a need to strengthen research on moringa to unlock its potential in Africa. Investments in research, innovation, and development can help address the many challenges that Africa faces and contribute to the transition towards sustainable and resilient food systems.
Keywords: neglected and underutilized species; NUS; orphan crops; M. oleifera; drumstick tree; horseradish tree; bibliometric; food security; livelihoods; climate change; SUSTLIVES